Anti/genotoxic, longevity inductive, cytotoxic, and clastogenic‐related bioactivities of tomato and lycopene. (22nd March 2018) - Fernández‐Bedmar, Zahira; Anter, Jaouad; Alonso Moraga, Ángeles
Abstract : The aim of this study was to evaluate some biological activities of tomato as well as lycopene and to consider a new nutraceutic value for this fruit regarding to the protection against genetic damage and as a chemopreventive agent. Genotoxicity, DNA‐protection against hydrogen peroxide, and lifespan properties of tomato and lycopene were assessed through wing spot test and longevity assay using the Drosophila in vivo model. Additionally, chemopreventive activity was investigated through cytotoxicity, DNA‐fragmentation comet and annexin V FITC/PI assays using HL60 in vitro model. Results showed that: (i) tomato and lycopene are not genotoxic and protect against H2 O2 ‐induced damage; (ii) with respect to the lifespan, tomato and lycopene are harmless at the lowest concentration; (iii) tomato is cytotoxic in a dose‐dependent manner, but not lycopene; (iv) tomato and lycopene do not induce internucleosomal DNA‐fragmentation although they induce significant clastogenic activity at low level in the leukemia cells. To sum up, tomato is a good candidate to be considered as a nutraceutical substance. Furthermore, synergistic action among other components within tomato matrix could be the cause of the health effects observed in this vegetable, which are not fully explained by lycopene. Environ. Mol. Mutagen. 59:427–437, 2018. © 2018 Wiley Periodicals, Inc.